Analysis of Spatial Relationships between Educational Facilities, Area, and Population Density in Lampung Province - Sari, Ratna Mustika; Samudra, Sena Andhika; Widayanti, Tika; Aulia, Rizqi; Ilyas, Ilyas (Ensiklopedia: Jurnal Pendidikan dan Inovasi Pembelajaran Saburai, 2025)
Indicators of sustainable development include equal access to education. However, when administrative region and population density are taken into account, educational resources are still unevenly distributed throughout Indonesia's numerous provinces. Lampung was chosen as the research location due to its rapid population growth over the last two decades, which has influenced demand for educational services and the distribution of other public resources. Lampung has 9.52 million people and covers 33,570 km². The importance of this study stems from the necessity to understand the geographical link between these variables in order to facilitate spatial data-based regional planning that is more equitable and efficient in terms of educational distribution. This study used statistical analysis, namely Pearson correlation analysis, to establish the degree of relationship between variables. The study discovered that the area has a Pearson correlation coefficient of 0.674 on the number of educational institutions. The Pearson correlation between population density and the number of educational facilities is -0.139, indicating a very weak relationship. The multiple correlation calculation of the relationship between area and population density with educational facilities provides a strong result of 0.745, suggesting that the larger the area in a region and the denser the population, the more educational facilities are required. Lampung's major districts are Way Kanan, Tulang Bawang, and Pesisir Barat, which rank third, fourth, and sixth respectively. However, in terms of educational facilities, Way Kanan, Tulang Bawang, and Pesisir Barat rank sixth, ninth, and fourteenth, respectively. Lampung province's population facilities and administrative areas remain significantly different.